Analysis of Consumer Perception Regarding Wardani Collection's Digital Marketing Content in the Bestee Program - Rudianto, Zeptanus Ricky Vernando (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: To analyze customers' perception of Wardani Collection’s digital marketing content on Instagram @pasardaya. Design/Method/Approach: Qualitative study using in-depth interviews to explore perceptions of digital marketing. Research Finding: Interviews revealed despite using social media, Wardani Collection did not have an increase in sales. Theoretical contribution/Originality: To increase the understanding of consumer perception on digital marketing on social media. Practitionel/Policy implication: Improving content quality, exploring diverse networks, and to consider the existence of online marketplace. Policymakers could use the findings of this study to better push digital literacy on the SMEs Community. Research limitation: short time span, limited resources, and a small data pool highlight the need for more extensive, longitudinal research